Will elephants soon disappear from West African savannahs? - Bouché, Philippe, author; Douglas-Hamilton, Iain, author; Wittemyer, George, author; Nianogo, Aimé J., author; Doucet, Jean-Louis, author; Lejeune, Philippe, author; Vermeulen, Cédric, author; Public Library of Science, publisher (Colorado State University. Libraries, 2011)
Precipitous declines in Africa's native fauna and flora are recognized, but few comprehensive records of these changes have been compiled. Here, we present population trends for African elephants in the 6,213,000 km2 Sudano-Sahelian range of West and Central Africa assessed through the analysis of aerial and ground surveys conducted over the past 4 decades. These surveys are focused on the best protected areas in the region, and therefore represent the best case scenario for the northern savanna elephants. A minimum of 7,745 elephants currently inhabit the entire region, representing a minimum decline of 50% from estimates four decades ago for these protected areas. Most of the historic range is now devoid of elephants and, therefore, was not surveyed. Of the 23 surveyed elephant populations, half are estimated to number less than 200 individuals. Historically, most populations numbering less than 200 individuals in the region were extirpated within a few decades. Declines differed by region, with Central African populations experiencing much higher declines (-76%) than those in West Africa (-33%). As a result, elephants in West Africa now account for 86% of the total surveyed. Range wide, two refuge zones retain elephants, one in West and the other in Central Africa. These zones are separated by a large distance (~900 km) of high density human land use, suggesting connectivity between the regions is permanently cut. Within each zone, however, sporadic contacts between populations remain. Retaining such connectivity should be a high priority for conservation of elephants in this region. Specific corridors designed to reduce the isolation of the surveyed populations are proposed. The strong commitment of governments, effective law enforcement to control the illegal ivory trade and the involvement of local communities and private partners are all critical to securing the future of elephants inhabiting Africa's northern savannas.
Keywords: elephant population; Loxodonta africana; West Africa